2021
DOI: 10.5653/cerm.2020.04035
|View full text |Cite
|
Sign up to set email alerts
|

Transforming growth factor-beta and liver injury in an arginine vasopressin-induced pregnant rat model

Abstract: Objective: Approximately 30% of preeclamptic pregnancies exhibit abnormal liver function tests. We assessed liver injury-associated enzyme levels and circulating transforming growth factor beta (TGF-β) levels in an arginine vasopressin (AVP)-induced pregnant Sprague-Dawley rat model.Methods: Pregnant and non-pregnant Sprague-Dawley rats (n=24) received AVP (150 ng/hr) subcutaneously via mini-osmotic pumps for 18 days. Blood pressure was measured, urine samples were collected, and all animals were euthanized vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 56 publications
1
0
0
Order By: Relevance
“…We further demonstrate alterations in kidney morphology including a mild increase in mesangium, mild glomerular crescents, and reduced Bowman’s space in AVP-treated rats. An earlier study performed by our lab assessed liver injury in the AVP rat model and found that serum expression of the liver injury enzymes arginase and 5′-nucleotidase, as well as transforming growth factor-2, was significantly higher in pregnant rats treated with AVP [ 129 ••]. Our findings are indicative of acute pregnancy-initiated liver dysfunction and support the utility of this model in the study of PE development.…”
Section: Rodent Models Of Pesupporting
confidence: 78%
“…We further demonstrate alterations in kidney morphology including a mild increase in mesangium, mild glomerular crescents, and reduced Bowman’s space in AVP-treated rats. An earlier study performed by our lab assessed liver injury in the AVP rat model and found that serum expression of the liver injury enzymes arginase and 5′-nucleotidase, as well as transforming growth factor-2, was significantly higher in pregnant rats treated with AVP [ 129 ••]. Our findings are indicative of acute pregnancy-initiated liver dysfunction and support the utility of this model in the study of PE development.…”
Section: Rodent Models Of Pesupporting
confidence: 78%